Retrospective study on growth in infants with isolated Robin sequence treated with the Tuebingen Palate Plate - Cornelia Wiechers (Orphanet Journal of Rare Diseases, 2021)
Abstract Background Children with Robin sequence (RS) are at risk of growth failure, mainly due to their increased work of breathing and feeding difficulties. Various conservative and surgical treatment approaches exist, but their impact on weight gain has not yet been adequately addressed. A functional treatment concept, used in our center for > 20 years, includes a pre-epiglottic baton plate (Tuebingen palatal plate) and intensive feeding training. Objective To investigate the effect of the Tuebingen treatment protocol on growth and weight trajectories during infancy. Methods This retrospective study analyzed longitudinal data from infants with isolated RS admitted to Tuebingen University Children’s Hospital, Germany between 1998 and 2019. Through our electronic patient database, we evaluated anthropometric parameters until reaching 1-year follow-up. Results are shown as median (IQR). Results In 307 infants analyzed, median Z-score for weight decreased from − 0.28 at birth to − 1.12 upon admission to our center at a median age of 22 days. Z-score then remained largely unchanged until discharge (Z-score difference, − 0.08), while the proportion of infants receiving tube feedings decreased from 55.1 to 13.7%. Z-score subsequently increased from − 1.17 at discharge to − 0.44 at the 1-year follow-up (p < 0.001). Conclusion Based on a comparatively large cohort, this functional treatment was associated with better weight gain and improved feeding. As RS infants often show postnatal growth failure, weight monitoring may be a valuable parameter for monitoring treatment effectiveness. Clinical Trial Registration Not necessary due to the retrospective design.